Assessment Mother`s Satisfaction of postpartum care - Naghizadeh, Somayyeh; Ebrahimpour Mirza Rezaie, Mehdi; Sehhati, Fahimeh; Atri Barzanje, Shirin; Ebrahimi, Hossein (Advances in Nursing & Midwifery, 2014)
Abstract Introduction: Nowadays patient’s satisfaction has an important role in medical care. Therefore consideration of patient’s expectation is necessary for improving quality of midwifery care. The aim of this study to assess patients’ satisfaction with postpartum care in teaching and nonteaching hospitals in Tabriz,Iran. Materials and Methods: This was descriptive comparative study in which 270 mothers were recruited from Alzahra, Taleghani and 29 Bahman hospitals in Tabriz. Mother`s satisfaction questionnaire was used to evaluate the satisfaction of four aspects of care (Physical, Providing necessary information, Ethical and Emotional). Results: Overall mother’s satisfaction rate of caregivers during postpartum was 78/5% and 86/3% in teaching and non-teaching maternity hospitals respectively. The results of this study showed that the mother’s satisfaction rate regarding providing necessary information by caregivers were very low. Mother’s dissatisfaction rate was 47% and 37% in teaching and non-teaching maternity hospitals respectively. There were a significant difference between mother’s satisfaction in aspect ethical in teaching and non-teaching maternity hospitals. Conclusion: Satisfaction rate in non teaching-hospitals was higher than teaching hospitals in both labor and delivery phase and one of the reasons for low satisfaction in teaching-hospitals is the presence of students and a large number of care givers in teaching hospitals. So that it is necessary to encourage care givers to give mothers necessary educations. This shows the importance more attention maternity services liable and directors in securing and promotion Mother`s health. Key words: Care, Satisfaction, Normal Vaginal Delivery, postpartum REFERENCES Azari S, Sehhati F, Ebrahimy H (2010).[Mothers’ satisfaction from cesarean cares in Public and Private Tabriz Hospitals in 2010]. Tabriz Nursing &Midwifery faculty, Iran MSc thesis. (Persian) Chunuan SK. (2002).Patient Satisfaction with Health Care Services Received during Intrapartum in One Regional Hospital in the Southern Part of Thailand. Unpublished PhD thesis, University Of Kentucky. Daff La, Lamping D,Ahmed LB. (2001). Evaluation satisfaction with maternity care in women from minority ethnic communities: development and validation of a Sylheti questionnaire. International Journal for Quality in Health Care . 17(3) 215-230. Fraser DM, Cooper MA (2003). Myles Textbook for Midwives .4th ed. London,Churchill Livingstone. Harvey S, Rach D, Stainton MC, Jarrell J, Brant R. (2002). Evaluation of satisfaction with midwifery care. Midwifery . 18 (4)260-267. Jafari F,Johari Z,Zayeri F, Ramazankhani A,Sayah Iran Z.(2006).[ Assessment client satisfaction and factors effective in health center]. Shahed Journals system (Bimonthly official publication medical Daneshvar), 14(66) 15-22. (Persian) Kabakian-Khasholian T, Campbell O, Shediac-Rizkallah M, Ghorayeb F. (2000).Women`s Experiences Of Maternity Care: Satisfaction Or Passivity. Social Science & Medicine , (51), 103-113. Mackey MC, Flanders Stepans ME. (1994). Women’s evaluation of their labor and delivery nurses. JOGNN , 23(5) 413-420. Mirmolaei S, Mehran A, Rahimi Ghasbeh S. (2004). [Mothers opinions concerning the importance of and their satisfaction with support received in the labor and delivery rooms]. Hayat . 9 (17) 41-47. (Persian) Mirmolaei S, Khakbazan Z, Kazemnead A, Azari M. (2007). [Prenatal care utilization rate and patients satisfaction]. Hayat . 13 (2) 31-40. (Persian) Ordibeheshti Khiaban M. (1998). [Women`s Expectation of Maternal Care Givers in Education Tabriz Maternity Hospitals].Un published Master`s thesis, Tabriz Nursing &Midwifery faculty, Iran. (Persian) Page LA(2000). The new midwifery science and sensitivity in practice , 1st ed.Churchill Livingstone, London. Peterson W. (2004). Adolescent Mothers`Satisfaction with Postpartum Nursing Care: Quantitative and Qualitative Approaches. Unpublished PhD thesis, Mc Master university. Robledo IJ. (1997). the Impact of Childbirth Preparation and Support on Labor and Birth Outcome. Unpublished PhD thesis, university of Rhode Island. Rudman A, El-Khouri B, Waldenstrom U. (2007).Women’s satisfaction with intrapartum care – a pattern approach. Journal of Advanced Nursing . 59(5) 474–487. Simbar M, Dibazari Z, Abedsaidi J,Alavimajd H(2005). [Assessment of quality of care in postpartum wards of Shaheed Beheshti Medical Science University hospitals,. Pajohande Journal ]. 10(43) 49-45.(Persian) Sharami SH, Zahiri H, Zendedel S. (2007). [Assessment the Client satisfaction in Prenatal Unit of Rasht Public Hospitals]. Gilan University of Medical Sciences Journal . 17 (66) 29-37. (Persian) Waldenstrom U,Brown S,Mclachlan H,Forster D,Brennecke S. (2000). Does team midwifey care increase satisfaction with antenatal, intrapartum, and postpartum care? A randomized controlled trial.Birth. 27(3)156-167. Zolfaghari B, Kabiri P, Oveic Gharan SH. (1997). [Development and Validation of an Instrument to measure Patient satisfaction with hospital services]. Esfahan University of Medical Sciences Journal . 3 (2) 136-142. (Persian)